70 Years later – what do we have to learn from Dietrich Bonhoeffer in Latin America today? - Caldas, Carlos (Stellenbosch Theological Journal, 2016)
The year 2015 marks the 70th anniversary of the execution of the Christian theologian and Pastor Dietrich Bonhoeffer. His theological legacy has been of great importance in Latin America, for both ecumenical/liberationist theologians and Evangelical theologians alike. But the main question is: after so many years, is Bonhoeffer’s theology still relevant in the Latin American theological context? In other words, ‘Who is Dietrich Bonhoeffer for us – in Latin America – today?’